Short Communication: Intra-Individual Microwear Variation: Deciduous versus Permanent Dentition - Tammy R. Gamza (Dental Anthropology Association, 2010)
This study compares microwear patterns on deciduous and permanent dentition within individuals. Number of features, total number of pits, mean pit breadth and mean scratch breadth are compared in 11 individuals aged 6-12 years. For each individual, the second deciduous molar and first permanent molar are used. Paired sample t-tests show no significant difference between deciduous and permanent enamel for any of the microwear features examined. This study suggests that differences in the physical and chemical structures of deciduous and permanent enamel are not sufficient to cause differences in microwear patterning. Any difference between juveniles and adults can be assumed to represent a true dietary difference rather than enamel structural differences.